LATE PLIOCENE VEGETATION AND CLIMATE OF THE LAKE BAIKAL REGION, SOUTHERN EAST SIBERIA, RECONSTRUCTED FROM PALYNOLOGICAL DATA - Demske D.; Mohr B.; Oberhänsli H. (My University, 2002)
Palynomorphs from a palaeomagnetically dated Late Pliocene sediment core (3.6–2.35 Ma) reflect highly variable climatic conditions and repeated expansion of steppe and boreo-alpine vegetation. Mixed coniferous forests (Picea, Tsuga, Pinus) with associated broadleaved taxa (Quercus, Corylus, Ulmus, Tilia) were affected by dry and cold intervals already between 3.48 and 3.39 Ma. Peak records of non-arboreal pollen types and spores, including subarctic-boreo-alpine Selaginella selaginoides, evidence advances of open vegetation, which can be correlated to glacial marine oxygen isotope stages. A cooling trend occurred from 3.15 Ma to 2.5 Ma, documented by cold–dry intervals and increased fluctuations of Picea and Pinus. Around 3–2.9 Ma the palaeoclimate variation pattern shifted towards cold–dry and warm–moist oscillations. Cooling strengthened after 2.89 Ma and severely restricted Tsuga development. Cool and oligotrophic limnic conditions are documented by abundant Gonyaulax dinoflagellate cysts in the interval 2.65–2.57 Ma. Due to decreasing precipitation extensive areas with open steppe and rock-steppe vegetation became permanently established after 2.62 Ma. Dry conditions became a dominant environmental factor in the Baikal region, coeval in time with the Red Clay–Loess shift in northern China. This climatic transition can be explained as a consequence of major intensification of Northern Hemisphere Glaciation around 2.75 Ma evidenced by marine records of ice-rafted debris.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен